The political influence of business in the European Union - Dür, Andreas <<[VerfasserIn]>>; Marshall, David <<[VerfasserIn]>>; Bernhagen, Patrick <<[VerfasserIn]>> (Ann Arbor University of Michigan Press, 2019)
"Many citizens, politicians and political activists voice concern about the political influence of business in the European Union (EU). But do business interests really pull the strings in Brussels? Contrary to what is widely expected, this book shows that business interests are no more influential than other interests in shaping contemporary EU policies. Andreas Dür, David Marshall, and Patrick Bernhagen present an original argument that stresses the role of public actors in facilitating or impeding interest groups' lobbying success. Novel data on a large number of legislative proposals on the EU's agenda and three case studies present strong support for this argument. In this process, The Political Influence of Business in the European Union offers new insights in how lobbying success depends on the demand and supply of information as well as new ideas on how to measure lobbying success. The book advances a fresh perspective on the question of business power and sheds new light on why business interests often lose in the policy struggle."
Literaturverzeichnis: Seite 189-207